Marketing Strategy of Mudharabah Deposit Products at Bank Syariah Indonesia - Kartika Marella Vanni (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This article discusses one of the safe investment instruments, namely mudharabah deposits at Bank Syariah Indonesia. Reviewing the marketing strategy that has been carried out and reviewing the SWOT analysis of the product. This article aims to find out the marketing strategies that have been carried out by BSI and their application in the field. This research uses descriptive qualitative research methods, involving BSI employees and related literature. The result of this study is that there are several marketing strategies used by BSI, namely through telemarketing, means of customer service by calling customers who have funds in BSI savings to place their funds in deposit products; social media, by offering deposit products with flayers uploaded via social media; mobile banking, by means of a mobile deposit feature that can be accessed through BSI mobile banking which is certainly safer.